RAS and BRAF genes as biomarkers and target for personalised colorectal cancer therapy: An update - Ooi, Zhuan Shern *; Pang, Siew Wai *; Teow, Sin Yeang * (College of Pathologists, Academy of Medicine Malaysia, 2022)
Colorectal cancer (CRC) remains among the most commonly diagnosed cancers and has been on the rise. It is also one of the most lethal diseases globally, being the third leading cause of cancerrelated death. Depending on the stages and disease conditions, CRC is treated by surgery, chemo-, radio-therapy, immunotherapy or in combination. However, these therapies have subpar results with unwanted side effects, hence continuous effort is ongoing to explore new type of therapeutic modalities. Among the sub-types of CRC, KRAS, BRAF and NRAS mutated CRC comprise approximately 43%, 10% and 3% of the total cases, respectively. These mutations are associated with tumour progression and anti-epidermal growth factor receptor (EGFR) treatment resistance. Due to their important role in CRC, these genes have thus become targets in the development of novel treatments. In this paper, we discuss the current and upcoming treatment on CRC by targeting these mutated genes, with more focus on KRAS and BRAF due to the higher occurrence of mutations in CRC.